Kilka uwag na temat dopuszczalności zawarcia ugody arbitrażowej i jej natury prawnej - Błaszczak, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This article relates to the issue of consent decree, which is made in proceedings in a court of conciliation. The article considers the situations where it is possible to make a consent decree, however it also profoundly analyses the legal nature of this question and its effects. The article concerns the problems connected with modification of a consent decree into an arbitration award as well. A consent decree exemplifies one of the methods of deciding cases in a court of conciliation.
Keywords: ugoda arbitrażowa; natura prawa